Adaptaciones Curriculares en TDAH en estudiantes de tercer grado de la Escuela de Educación Básica Particular Miguel Ángel Suarez, 2023-2024 - Yaguache Castro, Cynthia Tatiana (2024)
ADHD is a neurodevelopmental disorder that starts affecting in childhood and could persist into adulthood, it is characterised by deficit of attention, hyperactivity and impulsivity. People with ADHD usually struggle managing a group of important skills known as executive function. Therefore, it is essential that schools develop different teaching-learning metodologías that assist teachers in developing and implementing these strategies adequately. That is why, the main objective of this paper is to analyse the Curricular Adaptations in Attention Deficit and Hyperactivity Disorder in third grade students from the Escuela de Educación Básica Particular Miguel Ángel Suarez, 2023-2024. For the analysis, we used a qualitative approach, which permitted us to carefully identify the most relevant variables’ information; also, a non- experimental design was used; the methods we employed were the scientific, inductive, analytical, synthetic and descriptive; the interview and observation sheet enabled us to obtain specific information in a systematic and effective form; the sample population consisted of 27 students and 6 teachers. It was found that, although the teacher implemented curricular adaptations in her teaching plan, it did not comply with all the characteristics proposed and therefore, different difficulties were found in the students' learning. In addition, she described only some effects of ADHD, and consequently, she focused her work only on those she identified. In conclusion, curricular adaptations for children with Attention Deficit and Hyperactivity Disorder (ADHD) is the basis of the educational system to guarantee and provide access to education in an inclusive and adapted way, regardless of students’ individual abilities and needs. However, the lack of workshops and training prevents teachers from applying the curriculum correctly.